An association between subcutaneous fat mass accumulation and hypertension. (4th March 2021) - Goto, Kento; Yokokawa, Hirohide; Fukuda, Hiroshi; Saita, Mizue; Hamada, Chieko; Hisaoka, Teruhiko; Naito, Toshio
Abstract: Evidence to assess relationships between subcutaneous fat area (SFA) and lifestyle‐related diseases, including hypertension, remains limited. The aim of this study was to investigate the relationship between SFA and hypertension. This study was a single‐institution, cross‐sectional study of 1, 899 eligible Japanese participants who underwent health checkups between December 2016 and December 2018. All patients were measured for SFA and visceral fat area (VFA) by abdominal computed tomography (CT). SFA was divided into quartiles by gender, and multivariate logistic regression analysis was performed to estimate associations between SFA quartiles (Q) and hypertension. Mean age and SFA were 60.9 9 (standard devastation [SD]:12.0) years and 123.0 (56.9) cm 2 in men, and 60.6 (12.8) years and 146.6 (79.0) cm 2 in women, respectively. Risk of hypertension from multivariate regression modeling compared with the lowest quartile (Q) in both sexes was as follows: for men Q2 [odds ratio (OR), 1; 95% confidence interval (CI), 0.55‐1.51 ], Q3 (OR, 1.73; 95%CI, 1.17‐2.56), and Q4 (OR, 1.96; 95%CI, 1.31‐2.94); for women Q2 (OR, 0.87; 95%CI, 0.48‐1.58), Q3 (OR, 1.73; 95%CI, 1.02‐2.95), and Q4 (OR, 2.54; 95%CI, 1.51‐4.28). The optimal SFA cutoff value at risk of hypertension was 114.7 cm 2 in men and 169.3 cm 2 in women. The prevalence of hypertension was positively associated with SFA quartiles in both genders. The present results may indicate the necessity of considering not only VFA, but also SFA for the primary and secondary prevention of hypertension. Abstract : This study examined the association between subcutaneous fat area (SFA) and hypertension. SFA was divided into quartiles by gender, and multivariate logistic regression analysis was performed to estimate associations between SFA quartiles and hypertension. There was a positive correlation between subcutaneous fat area quartile and hypertension.